Biodiversity - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1998)
Biodiversity information: needs and options. Edited by D L Hawksworth and P M Kirk. 1997. 194 pp. UK£ 35. Publishing Division CAB International Wallingford Oxon, OX10 8DE UK. Fax: +44 1491 833508, Email: cabi@cabi.org. http://www.agricta.